Pathophysiology of pulmonary function anomalies in COVID-19 survivors - Pierantonio Laveneziana (European Respiratory Society, 2021)
Coronavirus disease 2019 (COVID-19) is a disease caused by a new coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-​2), and the predisposing and protecting factors have not been fully elucidated. COVID-19 primarily impacts the respiratory system, and can result in mild illness or serious disease leading to critical illness requiring admission to the intensive care unit due to respiratory failure. After hospital discharge, the more commonly described pulmonary function anomalies are alterations in diffusing capacity and the loss of lung volume. Reduction of inspiratory muscle contraction may also be underestimated. This article will focus on the pathophysiology of pulmonary function anomalies in COVID-19 survivors. We will discuss current advances and provide future directions and also present our perspective on this field.